KORELASI ANTARA RASIO NEUTROFIL/LIMFOSIT DENGAN KADAR C-REACTIVE PROTEIN PADA PENDERITA TUBERKULOSIS PARU - Aufani, Destia; Azzahra, Larasabella; Supriyanto, Supriyanto; Fatayati, Imma; Nuswantoro, Ari (Poltekkes Kemenkes Bandung, 2023)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and can persist in all parts of the body. Laboratory tests used to determine the level of inflammation in TB sufferers include the neutrophil/lymphocyte ratio (RNL) and C-reactive protein (CRP) levels. The RNL value is the ratio of the absolute number of neutrophils and the absolute number of lymphocytes, while CRP is an acute phase protein produced in the liver, and its levels increase within 6 hours in acute inflammation. The aim of this study was to determine the relationship between RNL and CRP in pulmonary TB patients. This research was a descriptive study with a cross-sectional design carried out from April to June 2021 at the Lung Health Services Integrated Service Unit, West Kalimantan Province. The number of samples was determined using a purposive sampling technique, with the criteria being newly diagnosed TB patients who had positive BTA, positive TCM and positive X-ray results, resulting in 48 samples. CRP levels were measured using the latex agglutination method, while the number of neutrophils and lymphocytes used the impedance method. Analysis was carried out using the Shapiro-Wilk normality test and Kendall's tau b correlation test. Statistical analysis using the Kendall's tau b correlation test obtained a significant value of 0.000 (<0.05), which means there was a relationship between RNL and CRP levels in pulmonary TB patients with a correlation coefficient of 0.489, which means the relationship between the two variables is enough.